Blue box. Volume 6 - Miura, Kouji (Manga author) (Shonen Jump manga., 2023)
"As summer draws to an end, Taiki realizes he may never be able to close the gap between himself and Chinatsu. He takes her to the beach to celebrate her birthday anyway, hoping to cheer her up after a grueling loss. However, their adventure goes awry when an unexpected storm forces them closer than ever before!"--